2011
DOI: 10.1089/dna.2010.1097
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Alpha-Albumin (Afamin) Promoter Is Differentially Regulated by Hepatocyte Nuclear Factor 1α and Hepatocyte Nuclear Factor 1β

Abstract: Alpha-albumin (AFM), a member of the albumin gene family that also includes albumin, alpha-fetoprotein, and vitamin D-binding protein, is expressed predominantly in the liver and activated at birth. Here, we identify two hepatocyte nuclear factor 1 (HNF1)-binding sites in the AFM promoter that are highly conserved in different mammals. These two sites bind HNF1a and HNF1b. The distal site (centered at À132, relative to AFM exon 1) is more important than proximal site (centered at À58), based on HNF1 binding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…[26][27][28][29][30] Previous studies indicated that the 3.2-kb region upstream of the rat GS gene (À3,150 to þ59) could confer pericentral expression of a linked reporter gene in Tg mice. 31 To test whether the upstream enhancer of the rat GS gene exhibited pericentral activity by itself, this enhancer was cloned as a 400-basepair (bp) fragment (as previously defined 21 and which will be referred to as RGS e ) and fused to the heterologous human b-globin promoter linked to the mouse H-2D d reporter gene (bgl-D d ). We have used bgl-D d extensively to monitor gene expression in cells and Tg mice; this cassette is inactive in all mouse tissues, but is highly responsive to linked enhancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] Previous studies indicated that the 3.2-kb region upstream of the rat GS gene (À3,150 to þ59) could confer pericentral expression of a linked reporter gene in Tg mice. 31 To test whether the upstream enhancer of the rat GS gene exhibited pericentral activity by itself, this enhancer was cloned as a 400-basepair (bp) fragment (as previously defined 21 and which will be referred to as RGS e ) and fused to the heterologous human b-globin promoter linked to the mouse H-2D d reporter gene (bgl-D d ). We have used bgl-D d extensively to monitor gene expression in cells and Tg mice; this cassette is inactive in all mouse tissues, but is highly responsive to linked enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…Protein concentrations were determined using the bicinchoninic acid (BCA) protein assay (Pierce, Rockville, IL). Labeling of annealed oligonucleotides (Table 1) (Integrated DNA Technologies, Inc., Coralville, IA) with 32 P and electrophoretic mobility shift assay (EMSAs) were carried out as previously described 21…”
Section: Methodsmentioning
confidence: 99%
“…Two hepatocyte nuclear factor 1 (HNF1)-binding sites binding HNF1α and HNF1β have been identified in the afamin promoter. Expression studies in mice suggest that the different responsiveness of albumin gene family members is crucial for their liver expression [11]. More recently, a microarray study showed increased expression of transcription factor islet-1 levels (which is associated with increased β-cell function) to increase afamin expression 35-fold [12].…”
Section: Gene Regulation Of Afaminmentioning
confidence: 99%
“…Activity of either partner may differentially affect the target genes. 29 Should this occur in humans, and if both patients carried a point mutation, a dominant-negative effect of HNF1A/HNF1B heterodimers could account for the phenotype. Alternatively, interacting genes may participate in phenotypic heterogeneity.…”
Section: Renal Phenotypementioning
confidence: 99%